A new theory of regular functions of a quaternionic variable - Gentili, Graziano; Struppa, Daniele C. (Advances in mathematics (New York. 1965), 2007)
In this paper we develop the fundamental elements and results of a new theory of regular functions of one quaternionic variable. The theory we describe follows a classical idea of Cullen, but we use a more geometric formulation to show that it is possible to build a rather complete theory. Our theory allows us to extend some important results for polynomials in the quaternionic variable to the case of power series.